Genotypic and technological diversity of Brevibacterium linens strains for use as adjunct starter cultures in 'Pecorino di Filiano' cheese ripened in two different environments - Bonomo, Maria Grazia; Cafaro, Caterina; Salzano, Giovanni (Folia microbiologica, 2015)
Twenty-two Brevibacterium linens strains isolated from 'Pecorino di Filiano' cheese ripened in two different environments (natural cave and storeroom) were characterized and differentiated for features of technological interest and by genotypic methods, in order to select strains with specific features to be used as surface starter cultures. Results showed significant differences among strains on the basis of physiological and technological features, indicating heterogeneity within the species. A middle-low level of proteolytic activity was observed in 27.3 % of strains, while a small group (9.1 %) showed a high ability. Lipolytic activity was observed at three different temperatures and the highest value was detected at 20 °C with 13.6 % of strains, while an increase in temperature produced a slightly lower lipolysis in all strains. The evaluation of diacetyl production revealed that only 22.8 % of strains showed this ability, and most of them were isolated from product ripened in the natural cave. All strains exhibited only leu-aminopeptidase activity, with values more elevated in strains coming from the natural cave product. The combined analysis of genotypic results with the data obtained by the features of technological interest study established that the random amplified polymorphic DNA (RAPD) clusters obtained were composed not only of different genotypes but of different profiles based on technological properties too. This study demonstrated the importance of the ripening environment that affects the typical features of the artisanal product, leading to the selection of a specific surface microflora. Characterized strains could be associated within surface starters to standardize the production process of cheese, but preserving its typical organoleptic and sensory characteristics and improving the quality of the final product.
Keywords: Cheese; fermentace; životní prostředí; Environment; Brevibacterium; Genotype; zvířata; bakteriální proteiny; mikrobiologie životního prostředí; Food Microbiology; sýr; Fermentation; Cattle; Environmental Microbiology; Milk; skot; Bacterial Proteins; genotyp; Animals; mléko; potravinářská mikrobiologie